ANALISIS PENGGUNAAN MODAL KERJA : (Studi Kasus pada Perusahaan UD. Afimans Ende) - Azi, Hendriana Owa; Sayang, Sabulon; Marselina, Apriana (Jurnal Riset Ilmu Akuntansi, 2020)
This study aims to determine the use of working capital and working capital turnover by the UD company. Afimans Ende, during 2016 - 2018. This type of research used in this study is a quantitative descriptive qualitative research. The type of data used in this study is documentary data obtained through official documents owned by the UD company. Afimans Ende in the form of financial statements (balance sheet and income statement) in 2016 - 2018. The data source used is secondary data. Data collection techniques used in this study are the analysis of the efficiency of the use of working capital (return on working capital) and the analysis of working capital turnover using the activity ratio consisting of cash turnover, accounts receivable turnover, inventory turnover and working capital turnover. The results showed that based on the calculation of the efficiency of the use of working capital (return on working capital) UD. Afimans Ende during 2016 - 2018 is efficient because the annual rate of return on working capital is greater than 100%. While the results of calculations carried out using the activity ratio in 2016 - 2018 are less efficient because the results of the calculation of cash turnover, accounts receivable turnover and inventory turnover show turnover results below the standard measurement of the efficiency of working capital use. And working capital turnover is said to be very efficient because the results of its turnover are above the standard measurement of the efficiency of working capital use. Suggestions provided include UD. Afimans Ende needs to conduct operational analysis in determining spending in the form of cash, minimizing credit sales that will cause accounts receivable and increasing sales of existing inventory in the warehouse so that there is no accumulation of inventory in the warehouse which will incur maintenance and maintenance costs.